The myth of the emptied land: biblical conquest and American nationalism - Hawk, L. Daniel (Word & world, 2017)
Many readers of the biblical narrative find in the events of the past parallels to the actions of their own history, connecting the two. Here the narrative of Joshua and the Israelites is linked with American history, especially with the treatment of Native Americans.